“Sacred” territories of artisanal fishing in João Pessoa: identities and sacralization of public spaces at the Festival of São Pedro Pescador - Baez, Gustavo Cesar Ojeda (2020)
This article aims to analyze the strategies sacredness of coastal areas, linked to religious festivals of artisanal fishermen from Joao Pessoa (PB). We understand that such parties create new territorialities and diversified forms of use for public spaces. In this way, in a first moment, we will characterize the traditional fishing communities, and their connections with the popular festivals, attentive to the discussion that surrounds the concept of popular religiosity. Secondly, we will concentrate on the festival ethnography of the Festival of São Pedro Pescador, that involves two fishing communities. At the end, we intend to demonstrate that these sacralization processes of public spaces and creation of fishing territories are social strategies of resistance and cultural reproduction of these communities.